ETR : Naarabelle Facespa / Nurfarahain Mohamad Fauzi ... [et al.] - Mohamad Fauzi, Nurfarahain; Mokhtar, Nurin Nazirah; Kairuddin, Nurul Nadia; Dasan Sandin, Priscillia Durrie; Ibrahim, Siti Nur Aisya (2019)
This report is focused on a case study of the company, Naarabelle Facespa that located at Kota Damansara, Petaling Jaya, Selangor. For this purpose, the team have an interview session with the owner about the company information and do a SWOT analysis.